Operational matrix for solving fractional differential equations with Erdelyi-Kober differential operator - Md Nasrudin, Farah Suraya; Chang, Phang; Mahadi, Shafaruniza; Arbin, Norazam (2024)
The operational matrix based on shifted Legendre polynomials is used in this study to solve Erdelyi-Kober (EK) fractional differential equations. To do this, we derive the analytical expression for polynomial for E-K derivative of polynomial